An evaluation of translation procedures with special reference to Xitsonga and English : the case of natural science and technology dictionary - Mabasa, Patricia Tinyiko (My University, 2009)
Refer to the document
Thesis (M.A. (Translation studies and linguistics)) -- University of Limpopo, 2009
Keywords: Tsonga language; English language; Tsonga language -- Dictionaries -- English; English language -- Dictionaries -- Tsonga